2001
DOI: 10.1021/om0102955
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure of Yttrium and Lanthanide Bis(phosphinimino)methanides

Abstract: Reaction of K{CH(PPh 2 NSiMe 3 ) 2 } (1) with anhydrous yttrium or lanthanide trichlorides leads to [{CH(PPh 2 NSiMe 3 ) 2 }LnCl 2 ] 2 (Ln ) Y (2a), Sm (2b), Er (2c), Dy (2d), Yb (2e), Lu (2f)). The single-crystal X-ray structures of these complexes show that the methine carbon is bound to the lanthanide atom. This is supported by DFT calculations, which show a comparable interaction. Due to the similar ion radii of the lanthanides, the single-crystal X-ray structures of 2a-f are isostructural. Further reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
69
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 65 publications
(64 reference statements)
5
69
0
Order By: Relevance
“…The distances between the central carbon atom (C1) and the lanthanide atom [2.697(4) (2 a), 2.875(4) (2 b), 2.771(3) (2 c), 2.685(3) (2 d), 2.647(4) (2 e)] are longer than average Ln-C distances; however, a resultant tridentate coordination of the ligand is observed as previously. [28][29][30] In contrast with the results obtained by . [37] One of the silicon atoms in this kind of groups (Si6) approaches more closely to the metal center than the others [Ln-Si6 3.1331(13) ( 2 La{NA C H T U N G T R E N N U N G (SiHMe 2 ) 2 }] (3.261(2) vs 3.472(2) for one of the two independent molecules in the unit cell).…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…The distances between the central carbon atom (C1) and the lanthanide atom [2.697(4) (2 a), 2.875(4) (2 b), 2.771(3) (2 c), 2.685(3) (2 d), 2.647(4) (2 e)] are longer than average Ln-C distances; however, a resultant tridentate coordination of the ligand is observed as previously. [28][29][30] In contrast with the results obtained by . [37] One of the silicon atoms in this kind of groups (Si6) approaches more closely to the metal center than the others [Ln-Si6 3.1331(13) ( 2 La{NA C H T U N G T R E N N U N G (SiHMe 2 ) 2 }] (3.261(2) vs 3.472(2) for one of the two independent molecules in the unit cell).…”
mentioning
confidence: 58%
“…Thus, [Ln{CH(PPh 2 NSiMe 3 ) 2 }{N-A C H T U N G T R E N N U N G (PPh 2 ) 2 }Cl] species are active catalysts for the ring-opening polymerization of e-caprolactone and the polymerization of methyl methacrylate, [30] whereas [Ln{CH(PPh 2 NSiMe 3 ) 2 }A C H T U N G T R E N N U N G (h 8 -C 8 H 8 )] was used as catalyst for the hydroamination/cyclization reaction. [28] Very recently, Doye et al have reported on Ti-based catalysts for sequential hydroamination/hydrosilylation, [31] while we have recently communicated the synthesis-based on these results-of [La{NA C H T U N G T R E N N U N G (SiHMe 2 ) 2 } 2 {CH(PPh 2 NSiMe 3 ) 2 }] as a non-cyclopentadienyl lanthanide catalyst useable for the hydroamination/cyclization and the hydrosilylation reactions. [32] Furthermore, we also studied this system for sequential hydroamination/hydrosilylation catalysis, and our catalyst turned out to be significantly more active than the previously reported systems.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…[39,[43][44][45][46][47][48] Recently, we introduced the bis(phosphinimino)methanide {CH(PPh 2 NSiMe 3 ) 2 } À , which has been used previously by a number of research groups in main-group and transition-metal chemistry, [63][64][65][66] into yttrium and lanthanide chemistry as a replacement for cyclopentadienyl. [51,[67][68][69][70][71][72][73][74][75] In general the CH 2 (PPh 2 NSiMe 3 ) 2 ligand is very easily accessible. It can be made in a Staudinger reaction in a few hours without solvent from commercially available starting materials.…”
Section: }Laa C H T U N G T R E N N U N G (Bh 4 ) 2 a C H T U N G T Rmentioning
confidence: 99%
“…First, K{CH(PPh 2 NSiMe 3 ) 2 } was treated with anhydrous yttrium trichloride to give the known dimeric complex [{CH(PPh 2 NSiMe 3 ) 2 }YCl 2 ] 2 . [67] In situ prepared [{CH(PPh 2 NSiMe 3 ) 2 }YCl 2 ] 2 was then treated with NaBH 4 to give compound 2 in good yield (Scheme 1). [80] Because the 3 ] for the syntheses of 1 and 3 was obtained from LnCl 3 and NaBH 4 , both synthetic routes are roughly equally time consuming.…”
Section: }Laa C H T U N G T R E N N U N G (Bh 4 ) 2 a C H T U N G T Rmentioning
confidence: 99%